THE EFFECT OF WORKLOAD ON THE PERFORMANCE OF CORRECTIONAL OFFICERS AT THE CLASS IIA LANGKAT NARCOTICS CORRECTIONAL INSTITUTION AND THE CLASS III LANGKAT YOUTH CORRECTIONAL INSTITUTION - Rafael Arapenta Perangin-Angin; Naniek Pangestuti (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effect of workload on the performance of correctional officers at Class IIA Langkat Narcotics Correctional Institution and Class III Langkat Youth Correctional Institution. The research is motivated by overcrowding conditions in both institutions, which increase work intensity and potentially affect officers’ performance. The population consists of all employees working in the two correctional institutions, and data were collected through online questionnaires. The study applies a quantitative approach, with data analyzed using simple linear regression with the assistance of statistical software. The results show that workload has a negative effect on the performance of correctional officers in both institutions. This means that higher levels of workload tend to reduce officers’ performance. The findings indicate that excessive duties and work pressure caused by overcrowding can affect officers’ productivity and effectiveness in carrying out their responsibilities. Therefore, this study recommends that prison management improve the task distribution system and work scheduling, while also providing training and psychological support for officers. These efforts are important to maintain officer performance, productivity, and well-being in a sustainable manner. Keywords: Workload; Performance; Correctional Officers; Narcotics Correctional Institution; Youth Correctional Institution